2020
DOI: 10.3390/microorganisms8081102
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Synthesized Alcaligenes Lipid A Shows a Potent and Safe Nasal Vaccine Adjuvant Activity for the Induction of Streptococcus pneumoniae-Specific IgA and Th17 Mediated Protective Immunity

Abstract: Effective and safe vaccine adjuvants are needed to appropriately augment mucosal vaccine effects. Our previous study demonstrated that lipopolysaccharide (LPS) from Peyer’s patch resident Alcaligenes stimulated dendritic cells to promote the production of mucosal immunity-enhancing cytokines (e.g., IL-6 and BAFF), thus enhancing antigen-specific immune responses (including IgA production and Th17 responses) without excessive inflammation. Here, we chemically synthesized Alcaligenes lipid A, the biologically ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 69 publications
0
20
0
Order By: Relevance
“…Only hexa-acylated A. faecalis lipid A 19 (hexa-AfLA) showed a TLR4-dependent immunostimulatory effect comparable to extracted A. faecalis LOS, indicating that hexa-AfLA 19 is the active principle of A. faecalis LOS [ 7 , 60 ]. An in vivo assay with mice confirmed that hexa-AfLA 19 exhibited a similar beneficial adjuvant effect (enhancement of antigen-specific IgA and IgG production) as A. faecalis LOS, without toxicity [ 61 , 62 ]. As a safe nasal vaccine adjuvant, the efficacy of hexa-AfLA 19 has been demonstrated in Streptococcus pneumoniae infection models [ 61 ], indicating that it is an extremely promising adjuvant for vaccines against infectious diseases.…”
Section: Lipid a Adjuvants Development Based On Bacterial–host Chemical Ecologymentioning
confidence: 99%
“…Only hexa-acylated A. faecalis lipid A 19 (hexa-AfLA) showed a TLR4-dependent immunostimulatory effect comparable to extracted A. faecalis LOS, indicating that hexa-AfLA 19 is the active principle of A. faecalis LOS [ 7 , 60 ]. An in vivo assay with mice confirmed that hexa-AfLA 19 exhibited a similar beneficial adjuvant effect (enhancement of antigen-specific IgA and IgG production) as A. faecalis LOS, without toxicity [ 61 , 62 ]. As a safe nasal vaccine adjuvant, the efficacy of hexa-AfLA 19 has been demonstrated in Streptococcus pneumoniae infection models [ 61 ], indicating that it is an extremely promising adjuvant for vaccines against infectious diseases.…”
Section: Lipid a Adjuvants Development Based On Bacterial–host Chemical Ecologymentioning
confidence: 99%
“…Immunization was performed as described previously ( 17 ). Briefly, on days 1, 7, and 17, the mice were intranasally immunized with 5 μg of ovalbumin (OVA) (Sigma-Aldrich) alone or 10 μg of Alcaligenes LPS or 1 μg of cholera toxin (CT) isolated from Vibrio cholerae (List Biological Laboratories, Campbell, CA, USA) in 15 µL of PBS and administered as 7.5 µL in each nostril of mice without anesthesia.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, on days 1, 7, and 17, the mice were intranasally immunized with 5 μg of ovalbumin (OVA) (Sigma-Aldrich) alone or 10 μg of Alcaligenes LPS or 1 μg of cholera toxin (CT) isolated from Vibrio cholerae (List Biological Laboratories, Campbell, CA, USA) in 15 µL of PBS and administered as 7.5 µL in each nostril of mice without anesthesia. One week after the final immunization, nasal wash, bronchoalveolar lavage fluid (BALF), serum, nasal passage, NALT, cervical lymphoid nodes (CLNs), and spleen were collected as previously described ( 17 , 18 ) and used for analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations